Perbandingan aplikasi Ijma’ antara Ulama’ Basrah dan Kuffah dalam analisis teks Arab - Sari, Dewi Masitoh Arum; Anggraini, Novia Retnowati; Hidayatullah, Achmad Diny (Maliki Interdisciplinary Journal, 2024)
Arabic language has two main keys that form the basis of its understanding, namely nahwu and shorf. The science of nahwu is the science that discusses the grammatical structure of the Arabic language. The proofs of nahwu science are as-sima'i, al-ijma', al-qiyas and istishab al-hal. Ijma' is an agreement between the scholars of Basrah and Kufa which can be used as a source of nahwu law if between them it does not conflict with the text and what is qiyaskan with the text. The difference of opinion between the scholars of Basrah and Kufa is what causes the variation in Ijma' Ushul Nahwu. This research study aims to reveal the agreement and differences in the use of ijma' ushul nahwu from the perspective of Basrah and Kufa scholars and its application in Arabic texts. The method used in this research is descriptive qualitative method through library research with reading and recording techniques. Primary references used are Kitab Al-Inshof Fii Masaail Al-Khilaf Baina Nahwayaini Al-Bashriyyiin wa Al-Kufiyiin and Kitab Safinatun Najaah, while secondary references are sourced from various references that are in accordance with the discussion in the study. The result of this research is that Basrah and Kufa scholars have the same agreement in the use of mubtada', khabar, ism maushul, fi'il mudhari' and huruf 'athaf. But they have differences in the use of fi'il lazim, fi'il muta'addi, huruf jar, na'at, man'ut, context and interpretation.